Labour market inequality in South Africa: a decomposition of changes in earnings from 2001 to 2011 - Hosking, Scott (School of Economics, 2017)
The relatively stable overall wage inequality in South Africa between 2001 and 2011 has hidden two distinct trends. Strong growth above the median for high wage earners has increased inequality at the top of the earnings distribution, whilst similarly, strong growth below the median has decreased inequality at the bottom of the distribution. This paper uses the 'task' approach alongside a Recentred Influence Function decomposition framework to explore the factors associated with this pattern of change. The findings suggest that routine-biased technical change and minimum wage laws enacted over the decade have important roles to play in the changes.